Effects of Motor Imagery Combined With Action Observation on Motor Function in Stroke Patients - Aisha Nakintu; Carmelo Mario Vicario; Lijuan Wang; Shuo Luan; Fengxue Qi (Journal of Integrative Neuroscience, 2025)
Stroke symptoms encompass sensory, cognitive, motor, and psychosocial dysfunctions, with motor impairment being the most prevalent. This impairment significantly contributes to functional incapacity and a diminished quality of life. Stroke rehabilitation strategies primarily aim to promote neural reorganization and motor skill recovery. Among these, motor imagery (MI) and action observation (AO) are distinct therapeutic techniques with unique mechanisms of action. This review begins by analyzing the strengths and limitations of each approach individually and argues that integrating MI and AO therapy could offer a more effective rehabilitation strategy. A thorough evaluation of relevant literature is presented, detailing methodologies, key findings, and implications. The objective is to elucidate the potential benefits and underlying mechanisms of combining these two therapies in stroke rehabilitation. In conclusion, the article advocates for the adoption of combined MI and AO therapy in neurorehabilitation.